EVALUASI PROSES PELAKSANAANPELAYANAN ANTENATAL PROGRAM JAMINAN PERSALINAN - , Titik Haryanti; , Prof. dr. Siswanto Agus Wilopo, SU, M.Sc., Sc.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Jampersal program is one of the efforts to achieve the MDGs. Crawl early detection of pregnancy and the risk of antenatal visits has reached the national target in Sukoharjo but MMR is still high. Therefore, it is necessary to see how the process of antenatal care Jampersal program. Objectives: To find out how the process services Jampersal programme by midwives private practice (MPP) and health center in sub Sukoharjo. Methods: This study is an evaluative research to design rapid assessment procedure, using a qualitative approach. Subjects were 6 midwives health center and 3MPP. Sampling was purposive sampling. Observation data retrieval in a midwifery practice in 16 pregnant women in health centers, 27 pregnant women at MPP and in-depth interviews with six midwives health center, three MPP, four patients and midwife health center coordinator. Results: The process of implementation of antenatal care Jampersalpatients for long examination, maternal relationship with the midwife, and the midwife treatment, MPP better than the heallth center midwives. The percentage amount of integrated antenatal health centermidwife and MPP varies and not all the examination of a given routinely to pregnant women. Routine antenatal care provided by health centermidwives and MPP are minimum service standards. Motivation midwives provided a variety of services one of which is due to funding.Obstacles/difficulties midwife health center providing services because less motivation of midwives and MPPdoes not yet support facility. Conclusion: Percentage of integrated antenatal care Jampersal program by the midwife clinic and MPP varies. Routine antenatal care is provided in accordance with the minimum service standards. Obstacles/difficulties midwife health center providing services because less motivation of midwives and MPP does not yet support facility but implicitly the same motivation, namely the problem of funding.